2011
DOI: 10.1016/j.curtheres.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 1 Minimum Alveolar Concentration Desflurane and 1 Minimum Alveolar Concentration Isoflurane Anesthesia in Patients Undergoing Craniotomy for Supratentorial Lesions

Abstract: In patients who underwent craniotomy for supratentorial lesions, patients who received 1 MAC desflurane-based anesthesia had earlier postoperative cognitive recovery and postoperative neurologic examination compared with patients who received 1 MAC isoflurane-based anesthesia. The observed benefits of early recovery from anesthesia, however, should be considered with risks such as higher MAP in patients administered 1 MAC desflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…Of note is the fact that the highest decrease in CPP was observed in the third period of the experiment at over 2/3 MAC while the absolute values of CPP noted then were below 60mmHg, which is considered safe. The available literature contains only a few clinical studies directly assessing the effect of desflurane on CPP [16][17][18]. The findings of the study analysing the effect of 0.5 and 1.0 MAC isoflurane, sevoflurane and desflurane on ICP and CPP in children are comparable with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Of note is the fact that the highest decrease in CPP was observed in the third period of the experiment at over 2/3 MAC while the absolute values of CPP noted then were below 60mmHg, which is considered safe. The available literature contains only a few clinical studies directly assessing the effect of desflurane on CPP [16][17][18]. The findings of the study analysing the effect of 0.5 and 1.0 MAC isoflurane, sevoflurane and desflurane on ICP and CPP in children are comparable with our results.…”
Section: Discussionsupporting
confidence: 81%
“…The use of desflurane in neuro anaesthesia is controversial as it produces cerebral vasodilation. However some studies confirm that the effects of desflurane on ICP and CBF are similar to isoflurane [3].…”
Section: Introductionmentioning
confidence: 86%
“…Sample size calculation, to achieve 80% power of the study, was on the basis of the previous study investigating the recovery charecteristics of desflurane, which demonstrated the mean time to achieve Aldrete score ≥8 as 9.58 ± 6.13 min. [ 1 ] We determined that 27 patients would be required for each group to detect 80% difference (8 min) in the time taken to achieve an Aldrete score of 9, using α and β values of 0.05 and 0.2. We chose to detect 80% difference as a smaller change would be clinically insignificant.…”
Section: Methodsmentioning
confidence: 99%
“…In neurosurgery, it may facilitate early post-operative neurological assessment. [ 1 2 ] Scalp block can blunt the haemodynamic response to noxious stimuli, decrease the amount of opioids and reduce post-operative pain[ 3 4 ] facilitating smooth and early emergence. Dexmedetomidine provides good perioperative haemodynamic stability, decreases the requirement of intraoperative opioid and has minimal effect on ICP.…”
Section: Introductionmentioning
confidence: 99%